Controlled release electrochemical synthesis and cytotoxicity study of copper(II) nanoparticles in copper(II) decanoate complex - M.Nordin, Norazzizi Atiqah; Samad, Wan Zurina; Kardia, Egi; Yahaya, Badrul Hisham; Yusop, M. R.; Othman, Mohamed Rozali (World Scientific Publishing Co. Pte Ltd, 2018)
In the present study, a controlled release electrochemical (CRE) technique based on the controlled release of Cu2+ ion from Cu anode in the presence of decanoic acid (HDe) has been used to synthesize Cu(II) decanoate (CuDe2) complex. The effect of applied voltages (1–10V) and electrolyte concentrations (0.1–2.0M CH3COONH4) during the electrolysis on the nanoparticles obtained was studied using TEM. The results reveal that small-sized nanoparticles (2±1nm) were obtained by using lowest applied voltage and CH3COONH4 concentration (1V and 0.1M, respectively). The smallest nanoparticle obtained was then used in the cytotoxicity study against A549 and HeLa cells. The synthesized complex gives moderate cytotoxic effect on the selected cells (IC50=15.85μM and 20.89μM, respectively) and low cytotoxic effect on normal cells (IMR90). Apoptosis is the mode of cell death based on the apoptosis assay that has been conducted.